World Hunger: Twelve Myths - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
F Moore Lappé, J Collins, and P Rosset. 1999. 280 pp. New Edition (see Spore 80).ISBN 1 85383 493 9 £12.99/ Euro 19.80Earthscan120 Pentonville Road, London, N1 9JN, UK.Fax: +44 171 278 1142Email: earthinfo@earthscan.co.uk